PELANGGARAN PERATURAN KEUANGAN,TEKANAN KEUANGAN,KINERJA KEUANGANDAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN: SINYAL PERUSAHAAN UNTUK MENDAPATKAN KEPERCAYAAN PEMANGKU KEPENTINGAN - Africano, Fernando; Parlindungan, Ricardo (Balance : Jurnal Akuntansi dan Bisnis, 2016)
The disclosure of corporate social responsibility (CSR) is the duty of an enterprise , it is worth to be known which factors affecting CSR disclosure.This study empirically examined the related theory of CSR with the data about CSR disclosure of non financial companies in the Indonesia Stock Exchange (IDX) .Variables used in the research are violation of financial regulations, financial distress andfinancial performanceto disclosure of corporate social responsibility (CSR).This research used quantitative method with secondary data. The secondary data obtained from Financial Services Authority (OJK) and Indonesia Stock Exchange (IDX).The testing done with with SPSS.The results shown that the financial distress affected CSR to CSR disclosure